Colours and Shapes First Skills with Ladybird - Lesley Clark (Italy Ladybird Books Ltd., 2006)
An essential early learning book to help build children's knowledge of everyday colours and shapes. They can have fun pointing to the pictures and saying the words. Are the things around the house green or blue, circle shaped or square?